Haven - Kay Hooper (Me. : Center Point Pub., 2012)
Another nightmare, in the woods this time. Different: she was running. Trying to escape. But the same ending: another dead girl ... Jessie, psychic investigator for a firm called Haven, has been estranged from her sister Emma for years. Now Emma is having nightmares, and the sisters discover there are secrets buried in Baron Hollow-- an evil that has been festering for years, one that's targeting Jessie and Emma one Read more...